STRATEGI KOMUNIKASI HUMAS DALAM MENINGKATKAN CITRA PERUSAHAAN PADA PT. NUTRIFOOD INDONESIA - Ashikin, Putri; Alfikri, Muhammad (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
With the strategy and resources owned by the company, a corporate communication strategy will help companies face the next decade. Corporate communications also help in following and positioning oneself at the forefront of any changes that may occur in the future through public relations or a public relations strategy. Because deciding on a convincing communication strategy is heavily influenced by the company's reputation. PT. Nutrifood Indonesia Medan is the object of research this time. Nutrifood Indonesia Medan has implemented an initiative aimed at turning negative public perceptions into positive ones, building a positive reputation for the future. Understanding the public relations strategy of Nutrifood Indonesia Pusat Medan is the main objective of this research. The theoretical framework of this research is the strategic theory of public relations and reputation building. Descriptive qualitative case studies, clearly outlined by the current research focus, constitute the research methodology used. Data is collected using primary sources, such as in-depth interviews and observations, and secondary sources, such as literature and documentation. The findings of this study indicate that PT. Public Relations of Nutrifood Indonesia Medan has implemented a PENSIL approach by using one of the signal strategies or both: 1. Publicity, 2. Event, 3. News, 4. Community, 5. Image, 6. Lobbying and Negotiation, 7. Social Responsibility.